FEATURES OF MARKETING ORGANIZATION IN LIGHT INDUSTRY ENTERPRISES (American Journal of Business Management, Economics and Banking, 2025)
This article looks at how marketing is organised in light industry firms and the peculiarities of this sector. Major factors such as the effect of marketing on business effectiveness and its flexibility to meet the contemporary issues, including digitalization, sustainable development, and increasing environmental concerns are discussed. Emerging marketing strategies and technologies such as artificial intelligence, big data, and e-commerce are also analyzed in this paper. A standard analysis together with a SWOT framework is used to reveal both the current issues and the promising marketing opportunities in the light.